The effects of dunite fertilization on growth and elemental composition of barley and wheat differ with dunite grain size and rainfall regimes - Rijnders, Jet; Vicca, Sara; Struyf, Eric; Amann, Thorben; Hartmann, Jens; Meire, Patrick; Janssens, Ivan; Schoelynck, Jonas (Frontiers in Environmental Science, 2023)
Enhanced weathering (EW) of silicate rocks is a negative emission technology that captures CO2 from the atmosphere. Olivine (Mg2SiO4) is a fast weathering silicate mineral that can be used for EW and is abundant in dunite rock. In addition to CO2 sequestration, EW also has co-benefits in an agricultural context. Adding silicate minerals to soils can significantly improve crop health and growth as the weathering releases elements such as silicon (Si) that can stimulate crop growth and increase stress resistance, a co-benefit that is becoming increasingly important as global warming proceeds. However, dunite also contains heavy metals, especially nickel (Ni) and chromium (Cr), potentially limiting its use in an agricultural context. In this study, we investigate the influence of dunite addition on growth of wheat and barley in a mesocosm experiment. We amended the soil with the equivalent of 220 ton ha-1 dunite, using two grain sizes (p80 = 1020 µm and p80 = 43.5 µm), under two rainfall regimes (each receiving the same amount of 800 mm water y−1 but at daily versus weekly rainfall frequency). Our results indicate that the amendment of fine dunite increased leaf biomass but only with daily rainfall. Aboveground biomass was significantly reduced with weekly rainfall compared to daily rainfall, but this reduction was slightly alleviated by fine dunite application for wheat. This indicates a positive effect of dunite during drying-rewetting cycles. For barley the negative effect of reduced rainfall frequency was not counterbalanced by dunite application. Contrary to our expectations, calcium (Ca) and Si concentrations in crops decreased with fine dunite application, while, as expected, magnesium (Mg) concentration increased. Coarse dunite application did not significantly affect crop nutrient concentrations, most likely due to its lower weathering rate. In contrast to what was expected, plant Ni and Cr concentrations did not increase with dunite application. Hence, despite high dunite application in our experiment, plants did not accumulate these heavy metals, and only benefited from the released nutrients, albeit dependent on grain size and rainfall frequency.